Glottodidactic control and regulation on the inter-individual level - Szczodrowski, Marian (Glottodidactica, 2020)
The subject of this discussion consists of selected concepts regarding the codematic foundations of foreign-language learning and cybernetic systems of foreign-language communication. The author focuses on processes of controlling, regulating, and directing foreign-language structures at the inter-individual level from the teacher to the learner. The control process, coupled with the process of basic information transfer, supports and strengthens it, both with linguistic (suprasegmental) means and extra-linguistic (visual) means. The basis of the regulation process are the effects of the coded structures of the learner, effects delivered to the teacher by the control system functioning through feedback. Glottodidactic direction includes the above two processes in order to transfer inaccurate structures, once corrected by the teacher, with the aim of re-decoding them and correctly assimilating them.